PENGARUH METODE BERMAIN TERHADAP HASIL BELAJAR HEADING SEPAK BOLA PADA PESERTA DIDIK SMP - Prasetyo, Rizki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The method used is an experimental method to study the form of true experimental design. The population in this study is a class VIII as much as 8 classes. The samples in this study using purposive sampling technique, as many as 70 people were divided into class VIII dam D totaling 35 persons as a class control while class VIII G totaled 35 as the experimental class. Data was analyzed using computerized systems as well as analysis by using t-test Based on t-test results on the class dick and experimental value 0,000 p value <0.05 then Ho is rejected (Ha acceptable) means that there is a significant improvement between the before and after treatment, in which the mean value of the difference in the experimental class (28.2) greater than the control group (8.7). Keywords: Playing, Learning Outcomes and Heading.